2015
DOI: 10.1111/oik.02512
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal by ungulates as an ecological filter: a trait‐based meta‐analysis

Abstract: Plant communities are often dispersal-limited and zoochory can be an efficient mechanism for plants to colonize new patches of potentially suitable habitat. We predicted that seed dispersal by ungulates acts as an ecological filter -which differentially affects individuals according to their characteristics and shapes species assemblages -and that the filter varies according to the dispersal mechanism (endozoochory, fur-epizoochory and hoof-epizoochory). We conducted two-step individual participant data meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
166
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(186 citation statements)
references
References 84 publications
(124 reference statements)
6
166
2
5
Order By: Relevance
“…Our findings are consistent with the results from the above mentioned studies, confirming that diaspores with appendages (e.g. hooks, awns, spines, bristles, hairs and wings) are more likely to be dispersed in the fur [1,27,44]. However, the lack of these diaspore structures (e.g.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings are consistent with the results from the above mentioned studies, confirming that diaspores with appendages (e.g. hooks, awns, spines, bristles, hairs and wings) are more likely to be dispersed in the fur [1,27,44]. However, the lack of these diaspore structures (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…Vremščica recorded in previous studies [30,42], were also found in the fur. In many studies the ability of diaspores to move with sheep transhumance has been observed [1,10,13,20,27]. However, no single study has sampled the high number of species demonstrated in the present work.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Besides techniques such as the transfer of seed-containing plant material or seeding (reviewed in [47]), the guidance of mobile livestock herds is suggested as a restoration measure improving an exchange of seeds over short and long distances [48]. The protection of the high capacity of domestic ungulate species in transferring seeds, particularly via faeces [49], becomes increasingly important with respect to ongoing land use and climate changes.…”
Section: Discussionmentioning
confidence: 99%